PERSEPSI DAN KESIAPAN GURU DALAM MENERAPKAN KURIKULUM MERDEKA BELAJAR DI MIS AT-TAQWA SAMBAS - Sri Endang Puji Astuti; Nuraini; Dewi Ferawati (JIP: Jurnal Ilmu Pendidikan, 2026)
ABSTRACT This study, entitled ‘Teachers’ Perceptions and Readiness in Implementing the Merdeka Belajar Curriculum at MIS At-Taqwa Sambas’, focuses on the following research questions: 1) What is the teachers’ understanding and interpretation of the Merdeka Belajar curriculum concept at MIS At-Taqwa Sambas?; What is the readiness of teachers to implement learning methods based on the Merdeka Belajar Curriculum at MIS At-Taqwa Sambas?; What are the factors influencing teachers’ perceptions and readiness in implementing the Merdeka Belajar Curriculum at MIS At-Taqwa Sambas? The research method employed in this study is qualitative, specifically field research. The data collection methods used consist of interviews, observation and documentation. The findings of this study can be summarised as follows: 1) Teachers’ understanding is a process of transition from the 2013 Curriculum to the Merdeka Belajar Curriculum, which emphasises freedom, flexibility, and the development of character as well as the unique potential of learners. This interpretation is reflected in the use of simple language, concrete examples, visual aids, interactive methods, and the integration of digital technology to make learning more meaningful and enjoyable. 2) Teachers’ readiness is supported by a combination of professional and pedagogical competencies, enhanced through training and the use of the teacher’s handbook as a reference. 3) Factors influencing teachers’ perceptions and readiness include personal and professional capabilities, institutional readiness, teaching experience, training, and the availability of relevant teaching materials. This study emphasises the importance of synergy between internal and external factors for the successful implementation of the Merdeka Curriculum within the school environment.